KHAIDIR SANGNGAJI DIFABEL YANG MENDIRIKAN PESANTREN BABUSSA’ADAH BAJO KABUPATEN LUWU SULAWESI SELATAN (1957 –2019) - Risma Widiawati Rusli (Al-Qalam, 2019)
“When there is a will, there will be a way”, this proverbs is held firmly by Khaidir Sangngaji, a person born with a disability from a simple family. Only determination and perseverance are the capital of advancing education in the area. In 1995 he began to demonstrate his leadership skills with his success in inviting the Bajo community to jointly build Islamic boarding schools. Based on this background, this research was conducted to reveal the biography of Khaidir Sangngaji and his struggle in the world of education. The study was conducted in Bajo Subdistrict, Luwu Regency, South Sulawesi, using the History method through an oral history approach. The results of the study showed that Khaidir Sangngaji who was born with disabilities with his arms and legs was stiff, had to fight hard to get an education. That condition led him to study in a pesantren in Java. In 1995, Khaidir Sangngaji returned to Luwu to serve in the Islamic Boarding School Datuk Sulaiman, while completing his undergraduate education. He then built a pesantren in his village, with the name Babussa'adah Bajo Modern Islamic Boarding School. Persuasive strategies carried out against regional leaders and the Luwu community and produces four important things, namely; 1) establishment of an organization of pesantren foundations, 2) fundraising for development 3) retrieval of strategic locations namely a level of Madrasah Tsanawiyah which was later transformed into Islamic boarding schools, and 4) bringing religious teachers to support pesantren. At present, Islamic boarding schools have cared for six levels of education, namely: Early Childhood Education (PAUD), Raudhatul Athfal, Ibtidaiyah Madrasah, Madrasah Tsanawiyah, Madrasah Aliyah, and Tahfidzul Quran.